Parents’ experiences on the management of the process after sexual abuse of their children in northern region of Turkey: Qualitative study - Nurten G. Bayrak; Sevda Uzun (Indian Journal of Psychiatry)
Background: Child abuse is a universal problem with medical, legal, and psychosocial dimensions that every child is at risk of encountering all over the world. Aim: The aim of this study was to evaluate the experiences of parents regarding the management of the process after sexual abuse of their children using a qualitative approach. Methods: In this qualitative study, semi-structured in-depth interviews were conducted with the parents of 15 children who were exposed to qualified sexual abuse living in a city in Northern Turkey. Criterion sampling method, one of the purposive sampling methods, was used to reach the sample group. Interviews continued until data saturation was achieved. All interviews were audio recorded and then transcribed. The data of the study were evaluated using thematic analysis. The study was conducted and reported according to the consolidated criteria for reporting qualitative research (COREQ) checklist. Results: In the analysis of the data, three themes (effects of child sexual abuse on the family, sexual abuse and process management, and attitudes and approaches to the child after sexual abuse), and nine sub-themes (mental, physical, social, reactions, difficulties experienced, coping, cognitive dimension, emotional dimension, behavioral dimension) were identified. Conclusion: As a result of the study, it was determined that parents were negatively affected psychologically by the sexual abuse of their children. This study reveals that the concept of family is very important in all aspects of the sexual abuse of children. As a result of the study, it was determined that families were not very effective in process management and some parents blamed themselves for the incident they experienced.